2021
DOI: 10.1093/icesjms/fsab142
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive output and potential recruitment of three fished southern king crab stocks from the Southern Atlantic Ocean

Abstract: The female reproductive output and potential recruitment (PR) were studied in three Argentinean southern king crab (Lithodes santolla and Lithodes confundens) stocks: in the Beagle Channel (BC), under an artisanal fishery pressure since 1930; in the San Jorge Gulf (SJG), under 10-years industrial fishing exploitation; and off the Atlantic coast of Isla Grande de Tierra del Fuego (TDF), under current exploratory regime. After evaluating their reproductive parameters, we suggest that these fisheries pass through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Marković et al [47] suggested that overfishing was the cause of the decreased size at 50% maturity (25.7 mm CL) observed for N. norvegicus in the South Adriatic Sea, the same size as the one found in the NW Mediterranean. Indeed, the abrupt decline in population abundances, which is observed in the NW Mediterranean Sea, caused by overfishing [4], can be followed by shifts in size and age at first maturity [48][49][50]. The current estimates of size at sexual maturity using the gonadal maturity of N. norvegicus (26.0 CL) confirm a decline in size at sexual maturity of about 4 mm CL in two decades, consistent with that reported by Vigo et al [20], and probably linked to relatively high fishing pressure [12].…”
Section: Discussionmentioning
confidence: 99%
“…Marković et al [47] suggested that overfishing was the cause of the decreased size at 50% maturity (25.7 mm CL) observed for N. norvegicus in the South Adriatic Sea, the same size as the one found in the NW Mediterranean. Indeed, the abrupt decline in population abundances, which is observed in the NW Mediterranean Sea, caused by overfishing [4], can be followed by shifts in size and age at first maturity [48][49][50]. The current estimates of size at sexual maturity using the gonadal maturity of N. norvegicus (26.0 CL) confirm a decline in size at sexual maturity of about 4 mm CL in two decades, consistent with that reported by Vigo et al [20], and probably linked to relatively high fishing pressure [12].…”
Section: Discussionmentioning
confidence: 99%
“…Southern king crab stocks demonstrate signs of overfishing in Chile and Argentina [67,68] probably due to male-only fishery management [69,70]. Therefore, stock enhancement, a feasible strategy to restore natural king crab populations [71], seems a management alternative for the near future.…”
Section: Discussionmentioning
confidence: 99%